The Effect of Pursed Lips Breathing Technique (PLBT) Administration on Oxygen Saturation in COPD Patients in the Intensive Care Unit - Normalia, Normalia; Andrianys, Irma; Asriadi, Asriadi; Mahyudin, Mahyudin (Jambura Nursing Journal, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a lower respiratory tract disease that can decrease oxygen saturation. Although COPD is not contagious, it has a significant impact and can lead to death. One nursing intervention that can be done to address this issue is the implementation of Pursed Lips Breathing Technique (PLBT) to improve lung ventilation, which in turn increases oxygen saturation levels. Objective: To determine the effect of pre and post implementation of Pursed Lips Breathing Technique (PLBT) on oxygen saturation in COPD patients in the ICU of Bhayangkara Makassar Hospital. Method: This study utilized a quantitative research design with a quasi-experimental Design One Group Pretest-Posttest. The sample size consisted of 16 individuals, selected using purposive sampling technique. Data was collected using an observation sheet. Result: The analysis using the Wilcoxon test yielded a p-value of 0.000 < 0.05, indicating that the alternative hypothesis (Ha) was accepted. There is a significant effect of pre and post implementation of Pursed Lips Breathing Technique (PLBT) on oxygen saturation in COPD patients in the ICU of Bhayangkara Makassar Hospital. Conclusion: There is a significant effect of pre and post implementation of Pursed Lips Breathing Technique (PLBT) on oxygen saturation in COPD patients in the ICU of Bhayangkara Hospital Makassar.